Política na organização: convivendo positivamente com o jogo do poder - Hoff, Irvando Luiz (2001)
This consideration about power in the organizations discuss alternatives to bring managers to have a more sociable co-existence with the political dimension of their work. It is not a goal to be achieved, but a continuous process of measuring the conflicts in order to reach better results for the company as well as the employees. Although it is not naturaly faced inside the organization, the power game always occurs when people is united around the same purpose. The departments are no exception. The power conflicts costs, mainly caused by lack of legitimacy, by excessive dependence, by low participation, by structures that stimulate segmentation, by an imperfect comunaction and by lack of political education, are extremely significant to the organizations. Therefore, facing the matter in a realistic way and developing attitudes and abilities to manage positively the divergent politics are basic tasks to the leader who desires to create a good working environment, as well as to rise his company world-wide.